OXIDATIVE STRESS IN THE PATHOGENESIS OF LEAD ACETATE INFLUENCE - Pershyn, O.I. (World of Medicine and Biology, 2014)
It was shown that the lead acetate poisoning of animals causes in lymphocytes and erythrocytes of blood oxidative stress and accumulation of lipid oxidation products. When the lead acetate poisoned animals were injected with vitamin E, oxidative stress was expressed less clearly. Different sensitivity of the enzymes of antioxidant system to the lead poisoning was found. The activity of superoxide dismutase and glutathione reductase in lymphocytes are reduced while the activity of glutathione peroxidase increases. The injections of vitamin E into animals affect the processes of lipid peroxidation and lead to changes in the activity of antioxidant enzymes in blood cells. In erythrocytes of rats injected with Pb(CH3COO)2 and vitamin E, glutathione peroxidase activity was normalized on the third day of the experiment while glutathione reductase and superoxide dismutase activity after 10 days. The results of these studies suggest an important role of vitamin E in the correction of disturbances in the functional activity of animals blood cells (erythrocytes, lymphocytes) due to effect of the lead cations.
Keywords: oxidative stress; lead acetate; erythrocytes; lymphocytes; vitamin E